Kesiapan Siswa Sekolah Dasar Mengikuti Pembelajaran Tatap Muka pada Masa Pandemi Covid 19 - Ni Ketut Pertiwi Anggraeni; Kristiningsih Kristiningsih (SAP (Susunan Artikel Pendidikan), 2023)
The implementation of education from the Early Childhood to Higher Education levels, has undergone online learning for the past 2 years since the Covid 19 Pandemic. With the increasing percentage of complete vaccine recipients, it opens up hope for schools, students, and parents to return to face-to-face schooling. The purpose of this study was to see the readiness of elementary school students to participate in Face-to-Face Learning (PTM) during the Covid 19 pandemic which was seen from two aspects, students' understanding of health protocols and student motivation. The survey was conducted on 30 elementary school students in 2022 where face-to-face learning began to be re-enforced, then the analysis was carried out qualitatively by describing the results of the survey and interviews. From the survey results it appears that elementary school students are ready to take part in Limited Face-to-Face Learning in terms of their understanding of health protocols and learning motivation. This research is expected to be a reference in preparing Face-to-Face Learning during the current Pandemic.